2022
DOI: 10.1002/hep.32326
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of hepatocyte nuclear factor 4 alpha activity in chronic liver diseases in humans

Abstract: Background and Aims Hepatocyte nuclear factor 4 alpha (HNF4α) is indispensable for hepatocyte differentiation and critical for maintaining liver health. Here, we demonstrate that loss of HNF4α activity is a crucial step in the pathogenesis of chronic liver diseases (CLDs) that lead to development of HCC. Approach and Results We developed an HNF4α target gene signature, which can accurately determine HNF4α activity, and performed an exhaustive in silico analysis using hierarchical and K‐means clustering, surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Integrin-linked kinase, critical for hepatocyte interactions with extracellular matrix, has been identified as a termination signal. 22 , 23 Recent studies from our laboratory have shown that HNF4α, the master regulator of hepatic differentiation, 24 , 25 is critical for re-differentiation of hepatocytes after proliferation and plays a critical role in termination of liver regeneration. 12 , 13 , 14 Previous studies have shown that defective termination of LR will result in significant hepatomegaly and death due to decline in liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin-linked kinase, critical for hepatocyte interactions with extracellular matrix, has been identified as a termination signal. 22 , 23 Recent studies from our laboratory have shown that HNF4α, the master regulator of hepatic differentiation, 24 , 25 is critical for re-differentiation of hepatocytes after proliferation and plays a critical role in termination of liver regeneration. 12 , 13 , 14 Previous studies have shown that defective termination of LR will result in significant hepatomegaly and death due to decline in liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HNF4α is the most abundant transcription factor in hepatocytes, and is downregulated in a stage‐dependent manner during hepatocarcinogenesis; its reduction is associated with EMT progression and poor prognosis 20–22 . We knocked up the HNF4α protein levels within the physiological range (Huh‐7: 1.4 ± 0.1, Hep3B: 2 ± 0.1) using SINEUP technology, in accordance with other studies that utilized SINEUP 23–27 .…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that HNF4α is the most abundant transcription factor in hepatocytes, and is downregulated in a stage‐dependent manner during hepatocarcinogenesis; its reduction is associated with EMT progression and poor prognosis. 20 , 21 , 22 We knocked up the HNF4α protein levels within the physiological range (Huh‐7: 1.4 ± 0.1, Hep3B: 2 ± 0.1) using SINEUP technology, in accordance with other studies that utilized SINEUP. 23 , 24 , 25 , 26 , 27 We revealed that stable increased expression of HNF4α protein in Huh‐7 and Hep3B cells generally decreased the expression of mesenchymal genes (including SNAI1 , SNAI2 , TWIST1 , CDH2 , VIM , and MMP14 ) and conversely increased the expression of epithelial ( CDH1 ) and hepatocytic late functional genes ( ALB ).…”
Section: Discussionmentioning
confidence: 83%
“…Raw fastq files were then aligned to the mouse genome (GRCm38) and counted using STAR software (20). DESeq2 (Version 1.28.1) in R Studio (Version 4.0.3, RStudio Team) was used for count normalization and differentially expressed gene (DEG) lists, as previously described (7).…”
Section: Rna-seq Data Acquisitionmentioning
confidence: 99%